Effects of acute alcohol on excitability in the CNS. (1st August 2017) - Harrison, Neil L.; Skelly, Mary Jane; Grosserode, Emma K.; Lowes, Daniel C.; Zeric, Tamara; Phister, Sara; Salling, Michael C.
Abstract: Alcohol has many effects on brain function and hence on human behavior, ranging from anxiolytic and mild disinhibitory effects, sedation and motor incoordination, amnesia, emesis, hypnosis and eventually unconsciousness. In recent years a variety of studies have shown that acute and chronic exposure to alcohol can modulate ion channels that regulate excitability. Modulation of intrinsic excitability provides another way in which alcohol can influence neuronal network activity, in addition to its actions on synaptic inputs. In this review, we review "low dose" effects [between 2 and 20 mM EtOH], and "medium dose"; effects [between 20 and 50 mM], by considering in turn each of the many networks and brain regions affected by alcohol, and thereby attempt to integrate in vitro physiological studies in specific brain regions (e.g. amygdala, ventral tegmental area, prefrontal cortex, thalamus, cerebellum etc.) within the context of alcohol's behavioral actions in vivo (e.g. anxiolysis, euphoria, sedation, motor incoordination). This article is part of the Special Issue entitled "Alcoholism". Highlights: Ethanol alters neuronal excitability and network activity in critical brain areas to produce its varied behavioral effects. Ethanol can alter synaptic transmission and intrinsic excitability in cerebellum, hippocampus, amygdala, and other areas. The effects of low (<20 mM) to moderate (20–50 mM) concentrations of ethanol arerelevant to social intoxication in humans. Ethanol has important effects that are pre- and postsynaptic, as well as non-synaptic in nature.